LATIHAN BOARD TAPS WITH BALL DAPAT MENINGKATKAN KEMAMPUAN UNDER THE BASKET SHOOT PADA PEMAIN BASKET - Ardani, Lalu Sinung; Canra Wira Kesuma, Dadang Warta (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
Basketball is game played by two teams that have a goal. Open the ball into the opponent’s basket as much as possible, and withstand the opponent’s attack so as not to enter the basket by throwing, dribbling, and shooting. The game of basketball is also required to master good shooting techniques because shooting techniques are a decisive factor in winning, basketball in addition to tactics, physical, mental, and uplifting. Based on the results of observations made by researchers to all students who are competing in DBL NTB 2019 researchers see that students when playing very often to under the basket shoot hit by the enemy when doing under the basket shoot. The purpose of this study was to determine whether there was an effect of Board Taps With Ball exercises on the ability of Under The Basket Shoot Extracurricular students of Basketball at public high school 1 sikur in 2020. The research design used was experimental research, this study used two variables, namely one independent variable and one dependent variable, the independent variable is the Tapas With Ball Board Exercise, while the dependent variable is Under The Basket Shoot. The population used is 15 players, the instrument used is the Hulfian ability shot test. The sampling technique uses porposiv sampling, from the results of data analysis from the Board Taps With Ball exercise using the t-test in which the alternative hypothesis (Ha) is accepted and the null hypothesis is rejected with details t count 4.938> t table 1.761 at a significant level of 5% then "There is an effect of board taps with ball training on the ability to shoot under the basket shoot extracurricular students basketball at public high school 1 Sikur in 2020